Influence of substrate bias voltage on the microstructure and mechanical properties of Ti-B-C-N coatings - Chee, Simon Wai Kin. (2013)
Thin coatings are often utilized in cutting tools and wear applications to improve their lifetime and performance. For decades, much emphasis has been placed on hardness properties. However, most applications not only require a coating to have high hardness but also other mechanical properties such as toughness which currently has limited data. Previous research has indicated the considerable potential of Ti-B-C-N coatings for application in mechanical components. However, limited studies have been done to investigate the quantitative toughness as well as the mechanical properties at elevated temperatures. Furthermore, the effects on negative substrate bias voltage on Ti-B-C-N coatings have not been well documented. Therefore, this study focuses on the influence of negative bias voltage on the hardness and fracture toughness of Ti-B-C-N coatings as well as the thermomechanical stability of Ti-B-C-N coatings. Ti-B-C-N coatings sputtered on silicon wafers were characterized and analyzed in terms of microstructure through X-ray diffraction, their hardness and toughness by nanoindention, microindentation and scanning electron microscopy. It was found that the Ti-B-C-N coating with applied bias of -150V yielded the optimal combination of hardness and toughness of 32.13 GPa and 2.67 MPam^(1/2) respectively. Based on findings in the present study, the recommended maximum service temperature limit is 300⁰C as the hardness property of Ti-B-C-N coating was found to be almost similar when annealed to 300⁰C as compared to as deposited Ti-B-C-N coatings. The enhancements in the mechanical properties were found to have a correlation with residual stress, grain size and bias voltage.